2005
DOI: 10.1088/0953-2048/18/6/002
|View full text |Cite
|
Sign up to set email alerts
|

Study of the crystal structure, superconducting and magnetic properties of Ru1−xFexSr2GdCu2O8

Abstract: Samples of the Ru 1-x Fe x Sr 2 GdCu 2 O 8 system with x = 0, 0.025, 0.05, 0.075, 0.1, and 0.2, were prepared and their structural, superconducting and magnetic properties were studied.Rietveld refinement of the X-ray diffraction patterns show that the Fe substitution occurs in both Ru and Cu sites. An increase of Fe concentration produces no significant changes in the bond angle Ru-O(3)-Ru, which is a measure of the rotation of the RuO 6 octahedra around the c-axis, and also in the bond angle φ, (Ru-O(1)-Cu),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The main objective of the present research is to extend and complement previous magnetization results obtained in the ðRu 1Àx Fe x ÞSr 2 GdCu 2 O 8Àδ [22] and to make a cross confirmation, between X-ray and Mössbauer results, of where do the iron atoms go into the structure of the Ru-1212 compound.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…The main objective of the present research is to extend and complement previous magnetization results obtained in the ðRu 1Àx Fe x ÞSr 2 GdCu 2 O 8Àδ [22] and to make a cross confirmation, between X-ray and Mössbauer results, of where do the iron atoms go into the structure of the Ru-1212 compound.…”
supporting
confidence: 55%
“…In the magnetization measurements of Escamilla et al [22], the samples showed ferromagnetic transition temperatures that decrease with increasing iron content. The Oxygen content…”
Section: Resultsmentioning
confidence: 91%
“…This behaviour is contrary to Sn and Nb as in Eu-1212 [26]. However, these characteristics are still more intriguing in the Ce, Eu-1222 [27] and Gd-1212 [28] compounds doped with iron where a decreasing of the magnetic moment in the Ru sublattice was observed. It is possible that this increase of the magnetic moment in the Ru/Co site may be due to an enhancement of the antisymmetric exchange, causing the effect that the spins are canted in the ab-plane as has been argued in several intermetallic and ruthenocuprate compounds [20,22,29,30], where a delicate balance among the subtle variations in composition, magnetic structure, and superconducting state may exist.…”
Section: Resultsmentioning
confidence: 97%